Halal collagen extraction from young and spent rabbit - Abdul Ghani, Nurul Fazliana (2016)
A Research was conducted to determine the percentage of collagen in young and spent rabbit muscles and legs bone. Nowadays, there are a lots of collagen production in industries but the main issues is the halal status of the collagen. A lots of collagen production in industries nowadays are the non- halal collagen from non- halal animals. Rabbit is the halal animal that have potential in collagen production. Biomedical industry have used young rabbit to extract hormone and enzyme while the carcass of rabbit will throw away. Rabbit breeder industry have thrown the spent rabbit carcass that do not suitable to eat any more. As alternative to improve and produce the halal collagen, these waste product from biomedical industry and rabbit breeder industry can be used in industry of collagen and indirectly will maximize the profit of both industries. This is because the rabbit carcass can be used as collagen sources instead of throw it away. The samples of young rabbit (2-3 months of age) and spent rabbit (> 1 year of age) were randomly selected. Collagen extraction was compared between the method 1 and method 2. Method 1 of collagen extraction was using Acetic Acid and Sodium Hydroxide while extraction of collagen in method 2 was using amyl alcohol, acetic acid and sodium chloride. The comparison of muscle and leg bone collagen content was conducted. The sample was compare to determine which sample produce more collagen. Besides, chemical analysis which is proximate analysis was conducted to evaluate the purity of the collagen and the chemical content on fresh samples. There were significantly different (P<0.05) for collagen extraction in both methods. The young rabbit bone in both method showed lower percentage of collagen extraction then spent rabbit bone. The percentage of young rabbit bone collagen are (13.59%) in method 1 and (9.0%) in method 2 while spent rabbit bone collagen are (15.35%) in method 1 and (9.39 %) in method 2. The young rabbit muscle collagen have lower percentage of collagen then spent rabbit muscle collagen in both methods. The percentage of young rabbit muscle collagen in method 1 is (18.04%) and spent rabbit muscle collagen is (18.21%) while young rabbit muscle collagen in method 2 is (12.74%) and spent rabbit muscle collagen is (14.12%). The time consume by method 1 to finish the extraction process is about 5 days while method 2 about 7days and above. The protein percentage in collagen from method 2 higher than the collagen from method 1 while the ether extraction percentage in method 1 is lower than method 2. That’s means, the collagen extraction from method 1 have lower percentage of fat. The lower the fat percentage, the high the purity of the collagen. Besides, the gelatine quality and characteristics test shown that there have no significant different in colour of gelatine. All the gelatine have yellowish in colour. The texture test shown that the gelatine come from muscle are more soft and sticky while gelatine from bone are more coarse and sticky. Based on the results, spent rabbit and muscle part have more collagen yield then young rabbit and bone part. However, extraction method 1 is more efficient to extract more collagen and have short time period of extraction than method 2.